발명 특허 - 디자인 특허 융합 분석을 통한기술기회 발굴 지원 방법론 - 송기식; 안재형; 박상영; 이성주; 김재훈 (대한산업공학회지, 2023)
Design patents contain as much unique information as utility patent data. The text dat+a of design patents is simpler compared to that of utility patents. The importance of design patent analysis is emerging to consider legal rights for designs. Despite the importance of design patents as a source of technological information, previous studies have rarely researched utility patents and design patents simultaneously. In addition, research using design patents is limited to macroscopic analysis, which results in a lack of systematic research to identify specific product development opportunities. To fill this research gap, this study proposes an approach for identifying new opportunities in product development through the convergence analysis of utility patents and design patents. This approach was applied to a case study involving a future mobility cockpit. In this approach, we initially gather data using the same search formula for both utility patents and design patents. Then, Utility patent-tree and Design patent-tree are derived based on text-mining and clustering analysis. Finally, by analyzing the similarity between the Utility patent-tree and the Design patent-tree, we present technology strategies for areas with high similarities and strategies for areas with low similarities. The results of this study will contribute to the discovery of opportunities in product technology, considering both technical and design concepts.
Keywords: Technology Opportunity; Patent Analysis; Future Mobility; Design Patents